Opposing roles of CLK SR kinases in controlling HIV-1 gene expression and latency - Subha Dahal; Kiera Clayton; Terek Been; Raphaële Fernet-Brochu; Alonso Villasmil Ocando; Ahalya Balachandran; Mikaël Poirier; Rebecca Kaddis Maldonado; Lulzim Shkreta; Kayluz Frias Boligan; Furkan Guvenc; Fariha Rahman; et al. (Retrovirology, 2022)
Plain Language Summary Identifying cellular factors that regulate HIV-1 RNA processing provides important insights into novel strategies to control this infection. Different members of the SR kinase family have distinct roles in regulating virus expression because they affect distinct steps of transcription/RNA processing. We identify inhibitors of these kinases that suppress HIV-1 gene expression and replication in multiple assay systems at nanomolar concentrations with limited or no cytotoxicity. Our results highlight the therapeutic potential of targeting the post-integration stage of the HIV-1 lifecycle to selectively enhance or reverse provirus latency. A greater understanding of the molecular mechanisms underlying the effects observed will facilitate the development of more targeted approaches to modulate HIV-1 latency on the path toward a “functional” cure for this infection.